Analysis of the Role of Mental Health in Social Interactions of University Students in Higher Education - Putri Dayani Ginting; Fiona Deanovans; Mhd. Virzha Nafandri utama (Cv. Digital Education Nusantara, 2026)
Abstract. Mental health is a critical determinant of the quality of social interactions among university students. Students who face mental health challenges such as anxiety, depression, and social isolation tend to experience difficulties in establishing meaningful interpersonal relationships. This study aims to analyze the role of mental health in shaping the social interaction patterns of university students through a systematic literature review of recent empirical studies. The findings reveal that students with good mental health demonstrate higher social interaction quality, indicated by openness in communication, empathy, and collaborative ability. Conversely, students experiencing mental health disturbances tend to withdraw socially, experience communication barriers, and report lower academic satisfaction. The study also identified that institutional factors such as campus social support, counseling availability, and peer group quality significantly moderate the relationship between mental health and social interaction. These findings underscore the importance of integrating mental health support programs into the academic environment of higher education institutions. Universities are recommended to strengthen counseling services, develop mental health literacy programs, and foster an inclusive social campus culture. Future research should examine the longitudinal effects and cultural differences in the relationship between mental health and social interaction among students in Indonesia. Keywords: mental health; social interaction; university students; higher education; psychosocial well-bein g